Detection of HCV-specific IFN-gamma responses in HCV antibody and HCV RNA negative injecting drug users - Flynn, J.; Sacks Davis, R.; Higgs, Peter; Aitken, C.; Moneer, S.; Suppiah, V.; Tracy, L.; Ffrench, R.; Bowden, S.; Drummer, H.; George, J.; Bharadwaj, M.; et al. (Kowsar, 2014)
Background: Detectable HCV-specific cellular immune responses in HCV antibody and RNA negative people who inject drugs (PWID) raise the question of whether some are resistant to HCV infection. Immune responses from people who have been exposed to hepatitis C virus (HCV) and remain anti-HCV negative are of interest for HCV vaccine development; however, limited research addresses this area. Objectives: In a cohort of HCV antibody and RNA negative PWID, we assessed whether the presence of HCV-specific IFN-γ responses or genetic associations provide any evidence of protection from HCV infection. Patients and Methods: One hundred and ninety-eight participants were examined longitudinally for clinical, behavioral, social, environmental and genetic characteristics (IFNL3 genotype [formally IL-28B] and HLA type). Sixty-one of the 198 participants were HCV antibody and RNA negative, with 53 able to be examined longitudinally for HCV-specific IFN-γ ELISpot T cell responses.Results: Ten of the 53 HCV antibody and RNA negative participants had detectable HCV-specific IFN-γ responses at baseline (18%). The magnitude of IFN-γ responses averaged 131 +/- 96 SFC/106 PBMC and the breadth was mean 1 +/- 1 pool positive. The specificity of responses were mainly directed to E2, NS4b and NS5b. Participants with (10) and without (43) HCV-specific IFN-γ responses did not differ in behavioral, clinical or genetic characteristics (P > 0.05). There was a larger proportion sharing needles (with 70%, without 49%, P = 0.320) and a higher incidence of HCV (with 35.1 per 100 py, 95% CI 14.6, 84.4, without 16.0 per 100 py, 95% CI 7.2, 35.6, P = 0.212) in those with IFN-γ responses, although not statistically significant. Half the participants with baseline IFN-γ responses became HCV RNA positive (5/10), with one of these participants spontaneously clearing HCV. The spontaneous clearer had high magnitude and broad Th1 responses, favorable IFNL3 genotype and favorable HLA types. Conclusions: This study demonstrated the detection of HCV-specific IFN-γ responses in HCV antibody and RNA negative individuals, with a tendency for HCV-specific IFN-γ responses to be associated with HCV exposure. The potential role of HCV-specific IFN-γ responses in those who remained HCV RNA negative is of value for the development of novel HCV therapeutics.